1996
DOI: 10.1007/bf02407051
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the development of nuclear power in Russia

Abstract: The future of nuclear power in Russia must be analyzed taking account of the trends which have appeared in recent years in the development of power in the developed and developing countries. In most developed countries the growth of energy consumption has slowed down, which to a large extent is due to effective energy conservation policy, whereas for the developing countries, characteristically, the demand for energy is increasing and there is a permanent growth of powergeneration capacity.In Russi~ the situat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The concept of using NPP to district heat (DH) production was investigated in the 1970s and the 1980s. Advanced studies were conducted in Central and Eastern Europe, where either Russian water-water thermal reactors (VVER) or light water-cooled graphite-moderated reactor (LWGR) were operated [3,4]. In addition, Bruce A NPP with Canada Deuterium Uranium (CANDU) reactor, generated electricity, district heat, and process heat.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of using NPP to district heat (DH) production was investigated in the 1970s and the 1980s. Advanced studies were conducted in Central and Eastern Europe, where either Russian water-water thermal reactors (VVER) or light water-cooled graphite-moderated reactor (LWGR) were operated [3,4]. In addition, Bruce A NPP with Canada Deuterium Uranium (CANDU) reactor, generated electricity, district heat, and process heat.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of using water at supercritical pressure in a reactor operating on thermal or fast neutrons are essentially obvious -the possibility of increasing the efficiency of a nuclear power plant from 33 to 44%, decreasing the amount of equipment and decreasing the amount of metal in the nuclear power system in the case of a direct-flow scheme, higher fuel-utilization indicators, and less construction [1,[3][4][5][6]. A great deal of experience has been accumulated in using supercritical-pressure water in ordinary (thermal) power engineering, where more than 120 units with power 300-1200 MW are operating in our country alone.…”
mentioning
confidence: 99%
“…It is shown that the temperature of the walls affects the start of the region with degraded heat transfer. A generalized relation, making it possible to determine to within 20% the onset of the degradtion of heat tansfer for different coolants (water, carbondioxide, freon-12), is proposed on the basis of the theory of thermodynamic similarity.The transition to supercritical parameters in water-cooled reactors is viewed as a natural continuation of the development of VVÉR reactors for the purpose of developing new-generation nuclear power plants [1][2][3][4]. The advantages of using water at supercritical pressure in a reactor operating on thermal or fast neutrons are essentially obvious -the possibility of increasing the efficiency of a nuclear power plant from 33 to 44%, decreasing the amount of equipment and decreasing the amount of metal in the nuclear power system in the case of a direct-flow scheme, higher fuel-utilization indicators, and less construction [1, 3-6].…”
mentioning
confidence: 99%
See 1 more Smart Citation